Measuring Liquidity as a Moderating Variable - Akhmadi Akhmadi; Enok Nurhayati; Anisa Rahmawati (International Business and Accounting Research Journal, 2023)
This study aims at the liquidity ratio as a moderating factor in the relationship between profitability and dividend policy. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange for the period 2008-2017. While the number of samples as many as 12 companies determined through the purposive sampling method. The analytical methods used are descriptive statistics, Moderated Regression Analysis (MRA), and hypothesis testing. The results of this study indicate that profitability has a significant effect on dividend policy. Meanwhile, Liquidity does not moderate the relationship between Profitability and Dividend Policy. The results of the study cannot be generalized due to the limitations of the research object only in the manufacturing sub-sector. In addition, the observed variables only use one proxy each. Further research should expand the object of research to several sub-sectors, and use several proxies for each of the variables studied.